2017
DOI: 10.1186/s12879-017-2415-8
|View full text |Cite
|
Sign up to set email alerts
|

Progressive cutaneous Cryptococcosis complicated with meningitis in a myasthenia gravis patient on long-term immunosuppressive therapy – a case report

Abstract: BackgroundCryptococcosis is an opportunistic infection caused by the encapsulated yeast Cryptococcus neoformans and most remarkably manifests in HIV-infected individuals, especially in the settings of very low CD4 count. Development of cryptococcosis in HIV-uninfected individuals is exceedingly rare and usually signifies a marked immunodeficiency. Cryptococcosis in association with myasthenia gravis or thymoma has been previously documented in only very few cases in the literature.Case presentationWe reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Case reports of opportunistic viral, bacterial, or fungal infections have been reported with the use of conventional immunosuppressants. 113,114 These new drugs-complement inhibitors, FcRn blockers, and monoclonal antibodies against CD19 or CD20-might substantially improve quality of life and diminish the adverse effects of long-term corticosteroids or the bone-marrow toxicity of current immunosuppressive drugs, but in several countries high costs are prohibitive. A 2020 Canadian pharmacoeconomic report on eculizumab concluded that, despite several limitations in the analysis, eculizumab could not be considered costeffective without considerable price reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports of opportunistic viral, bacterial, or fungal infections have been reported with the use of conventional immunosuppressants. 113,114 These new drugs-complement inhibitors, FcRn blockers, and monoclonal antibodies against CD19 or CD20-might substantially improve quality of life and diminish the adverse effects of long-term corticosteroids or the bone-marrow toxicity of current immunosuppressive drugs, but in several countries high costs are prohibitive. A 2020 Canadian pharmacoeconomic report on eculizumab concluded that, despite several limitations in the analysis, eculizumab could not be considered costeffective without considerable price reduction.…”
Section: Discussionmentioning
confidence: 99%